Trait determinants of impulsive behavior: a comprehensive analysis of 188 rats. Issue 1 (December 2018) - Soares, Ana; Esteves, Madalena; Moreira, Pedro; Cunha, Ana; Guimarães, Marco; Carvalho, Miguel; Raposo-Lima, Catarina; Morgado, Pedro; Carvalho, Ana; Coimbra, Bárbara; Melo, António; Rodrigues, Ana; et al.
Abstract Impulsivity is a naturally occurring behavior that, when accentuated, can be found in a variety of neuropsychiatric disorders. The expression of trait impulsivity has been shown to change with a variety of factors, such as age and sex, but the existing literature does not reflect widespread consensus regarding the influence of modulating effects. We designed the present study to investigate, in a cohort of significant size (188 rats), the impact of four specific parameters, namely sex, age, strain and phase of estrous cycle, using the variable delay-to-signal (VDS) task. This cohort included (i) control animals from previous experiments; (ii) animals specifically raised for this study; and (iii) animals previously used for breeding purposes. Aging was associated with a general decrease in action impulsivity and an increase in delay tolerance. Females generally performed more impulsive actions than males but no differences were observed regarding delay intolerance. In terms of estrous cycle, no differences in impulsive behavior were observed and regarding strain, Wistar Han animals were, in general, more impulsive than Sprague-Dawley. In addition to further confirming, in a substantial study cohort, the decrease in impulsivity with age, we have demonstrated that both the strain and sex influences modulate different aspects of impulsive behavior manifestations.